Study on Abrasion Resistance of Granite Manufactured Sand Concrete Based on Indoor Abrasion Tester - Li, Zhitang; Wang, Yuankuo; Yang, Xiaolong; Liang, Junlin; Chen, Yuanfeng; Pan, Minqiang (Coatings (Basel), 2025)
The long-term wear resistance of granite manufactured sand (HGY) concrete has not been sufficiently investigated. This deficiency makes it difficult to accurately predict and evaluate the service life and durability of such concrete pavements in practical engineering applications. Consequently, this study employed a self-developed indoor abrasion test device and combined it with scanning electron microscope (SEM) and X-ray diffraction (XRD) technologies. From the two dimensions of macroscopic performance and microscopic structure, the mechanisms’ influence of the effective sand ratio, stone powder content, and fine aggregate lithology on the wear resistance of HGY concrete were systematically investigated. The optimal content of the effective sand and stone powder content were determined, and the long-term evolution law of the wear resistance of HGY concrete was revealed. The results demonstrate that increasing the effective sand content will reduce the mass loss of concrete. When the stone powder content is 9%, the wear resistance of the concrete is optimal. The order of mass loss of different fine aggregate lithologies is river sand (HS) > limestone mechanism sand (SHY) > HGY, and the wear resistance of HGY is better than that of other fine aggregates. Increasing the effective sand content can enhance the bonding strength between the aggregate and the cement matrix and reduce the porosity, which is conducive to improving the wear resistance of the concrete. Under a relatively small stone powder content, as the amount of stone powder added increases, the pore structure becomes tighter, and the wear resistance of the concrete becomes better. Compared to HS, the manufactured sand (MS) containing stone powder can optimize the pore structure and hydration products of concrete, improve the pore structure of concrete, and improve the wear resistance.